2018
DOI: 10.1007/jhep04(2018)042
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence and hydrodynamic attractors in Gauss-Bonnet holography

Abstract: Abstract:We study the convergence of the hydrodynamic series in the gravity dual of Gauss-Bonnet gravity in five dimensions with negative cosmological constant via holography. By imposing boost invariance symmetry, we find a solution to the Gauss-Bonnet equation of motion in inverse powers of the proper time, from which we can extract high order corrections to Bjorken flow for different values of the Gauss-Bonnet parameter λ GB . As in all other known examples the gradient expansion is, at most, an asymptotic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 72 publications
(183 reference statements)
3
46
0
Order By: Relevance
“…To show how the MIS equations arise from a dual gravitational description, we focus on the Einstein-Gauss-Bonnet theory [53,54,103,104], which is a useful holographic toy model for analyzing thermal field theories at intermediate coupling strengths. The crucial feature of the theory, and of other higher-derivative theories, is the emergence of quasinormal modes with a purely relaxing, imaginary dispersion relation ω(k) [51,54,105]. As was demonstrated in [51,54], these modes reproduce many expected spectral properties of thermal theories in transition from strong, towards weak coupling.…”
Section: Müller-israel-stewart Theory and Higher-derivative Gravitymentioning
confidence: 71%
“…To show how the MIS equations arise from a dual gravitational description, we focus on the Einstein-Gauss-Bonnet theory [53,54,103,104], which is a useful holographic toy model for analyzing thermal field theories at intermediate coupling strengths. The crucial feature of the theory, and of other higher-derivative theories, is the emergence of quasinormal modes with a purely relaxing, imaginary dispersion relation ω(k) [51,54,105]. As was demonstrated in [51,54], these modes reproduce many expected spectral properties of thermal theories in transition from strong, towards weak coupling.…”
Section: Müller-israel-stewart Theory and Higher-derivative Gravitymentioning
confidence: 71%
“…The main focus of ref. [27] was on the possibility of recovering the full spectrum from the hydrodynamic derivative expansion, similar to recovering the non-hydrodynamic modes from asymptotic series via Borel resummation and resurgence [17,18,25]. The quasinormal spectrum in the holographic models with finite temperature T and non-vanishing chemical potential µ such as the one considered in ref.…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned in ref. [8] in the context of the discussion of the "unreasonable effectiveness" of hydrodynamics as an effective theory, many previous studies have reported the divergence of the derivative expansion in relativistic hydrodynamics [15,17,18,18,25]. Possibly, the asymptotic nature of the expansion appearing in those publications should be viewed as a reflection of the singular nature of the state about which this expansion is performed, rather than a generic property of the hydrodynamic gradient expansion itself.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48]) and calculated numerically to high orders in Refs. [8,16]. We adopt the Eddington-Finkelstein (EF) coordinate system which implements the symmetries of Bjorken flow with the following ansatz [3,[49][50][51]…”
Section: The Bulk Gravity Solution and Energy Densitymentioning
confidence: 99%
“…These coefficients ε (n) k have been included with this submission for the sectors Φ n with n = 0, e 1 , e 2 , 2e 1 , (e 1 +e 1 ), along with their corresponding exponential weights A i and characteristic exponents β n . For the hydrodynamic sector Φ 0 coefficients for the hydrodynamic expansion were taken from [16].…”
Section: Energy Density Of the Dual Theorymentioning
confidence: 99%